Benzodithiazole‐Based Hole‐Transporting Material for Efficient Perovskite Solar Cells. Issue 12 (24th October 2018) - Swetha, T.; Akhtaruzzaman, Md.; Chowdhury, Towhid H.; Amin, Nowshad; Islam, Ashraful; Noda, Takeshi; Upadhyaya, Hari M.; Singh, Surya Prakash
Abstract: We have designed and synthesized a family of three novel benzodithiazole‐based hole‐transporting materials (HTMs) named asBTT‐TPA, BTT‐OMe andBTT‐Me . These new HTMs are characterized by using 1 H, 13 C NMR, FTIR, elemental analysis, UV‐Vis spectrophotometer, and cyclic voltammetry. The photovoltaic performances of these HTMs were successfully evaluated in perovskite solar cells (PSCs). Consequently, the PSCs based onBTT‐TPA, BTT‐Me andBTT‐OMe HTMs showed Jsc of 12.81 mA cm −2, 11.87 mA cm −2, 13.85 mA cm −2, Voc of 0.88 V, 0.83 V, 0.87 V, a FF of 0.62, 0.63, 0.63 and the overall power conversion efficiency of (η) 6.99%, 6.20% and 7.44%, respectively. The easy synthetic route and purification technique provides the viability of these HTMs as future PSCs development. Abstract : Solar cells : Three simplest benzodithiazole‐based hole‐transporting materials (HTMs) named asBTT‐TPA, BTT‐OMe andBTT‐Me have been designed and synthesized. Among themBTT‐OMe exhibited high power conversion efficiency of 7.46%. This study will provide the way on how to design simplest HTMs compared to Spiro‐OMeTAD.